Knowledge mapping of B cell and atherosclerosis over the past 20 years: A bibliometric analysis - Tao Cheng; Yaping You; Bochao Jia; Huan Wang; Meng Lv; Xueping Zhu; Yuanhui Hu (Human Vaccines & Immunotherapeutics)
Atherosclerosis (AS) is the main underlying cause of cardiovascular disease, and B cells are considered a key immune cell type to regulate AS. So far, there is no bibliometric study on B cell and AS. This study aims to comprehensively analyze the scientific output about B cell and AS, summarize the literature characteristics, explore research hotspots, and point out emerging trends. We searched the literature from 2003 to 2022 from the Web of Science Core Collection (WoSCC) database. CiteSpace, VOSviewer, and the R package “Bibliometrix” were used for literature analysis and visualization. A total of 1,062 articles and reviews were identified. The number of annual publications generally showed an upward trend. The United States and China were the most productive countries. Medical University of Vienna was the most productive research institution, and Binder Christoph J. was the most productive author, who was also from Medical University of Vienna. “Arteriosclerosis Thrombosis and Vascular Biology” was the most published journal and the most frequently cited journal. The most cited reference was written by Caligiuri G (2002) in “Journal of Clinical Investigation.” The most frequent keywords were “inflammation,” “macrophages,” “cardiovascular disease,” “T cells,” “apoptosis,” “immunity,” “cytokines,” “lymphocytes,” etc. The trend topics were mainly focused on “immune infiltration,” “immunoglobulins,” and “biomarkers.” The complex role of B cell subtypes and a variety of B cell mediators is the main research direction at present. In-depth analysis of B cell-specific targets can provide new ideas and methods for the prevention and treatment of AS.